Individualities of cardiorespiratory responsiveness to shifts in respiratory homeostasis and physical exercise in homogeneous groups of high performance athletes - Mishchenko, V.; Shynkaruk, O.; Suchanowski, A.; Lysenko, O.; Tomiak, T.; Diachenko, A.; Korol, A. (Baltic Journal of Health and Physical Activity, 2010)
Background: It is known that high sports performances are based upon optimization of adaptation process. In order to achieve the above, one should provide a maximal account of individual vivid features of athlete's abilities, peculiarities of his/her physiological reactivity. The aim was to study individualities of sensitivity to shifts in respiratory homeostasis and responsiveness to high intensity physical exercises in homogeneous groups of high performance endurance athletes.